Imaging of Nerve Disorders in the Elbow - Gunio, Drew; Babaa, Ahmad; Bencardino, Jenny T. (Seminars in Musculoskeletal Radiology, 2022)
Neuropathies of the elbow represent a spectrum of disorders that involve more frequently the ulnar, radial, and median nerves. Reported multiple pathogenic factors include mechanical compression, trauma, inflammatory conditions, infections, as well as tumor-like and neoplastic processes. A thorough understanding of the anatomy of these peripheral nerves is crucial because clinical symptoms and imaging findings depend on which components of the affected nerve are involved. Correlating clinical history with the imaging manifestations of these disorders requires familiarity across all diagnostic modalities. This understanding allows for a targeted imaging work-up that can lead to a prompt and accurate diagnosis.
Keywords: neuropathy; ulnar nerve; radial nerve; median nerve